2011
DOI: 10.1111/j.1475-6773.2011.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Reporting in Qualitative, Quantitative, and Mixed Methods Health Services Research Articles

Abstract: Objectives Methodologically sound mixed methods research can improve our understanding of health services by providing a more comprehensive picture of health services than either method can alone. This study describes the frequency of mixed methods in published health services research and compares the presence of methodological components indicative of rigorous approaches across mixed methods, qualitative, and quantitative articles. Data Sources All empirical articles (n = 1,651) published between 2003 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(157 citation statements)
references
References 46 publications
7
137
1
3
Order By: Relevance
“…First, many mixed methods studies in health services research and implementation science do not clearly identify or provide a rationale for the sampling procedure for either quantitative or qualitative components of the study (Wisdom et al, 2011), so a primary recommendation is for researchers to clearly describe their sampling strategies and provide the rationale for the strategy.…”
Section: Discussionmentioning
confidence: 99%
“…First, many mixed methods studies in health services research and implementation science do not clearly identify or provide a rationale for the sampling procedure for either quantitative or qualitative components of the study (Wisdom et al, 2011), so a primary recommendation is for researchers to clearly describe their sampling strategies and provide the rationale for the strategy.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 One published metareview included an analysis of all published articles in 4 health services research journals, 15 and another aimed to review all published mixed methods studies within the area of health research. 16 The use of various mixed methods designs and techniques in published reports of healthcare research has been well summarized within the field of mental health, 17 but focused metareviews of published mixed methods studies within other topic areas in health research, such as cardiovascular diseases, are lacking.…”
Section: Use Of Mixed Methods Researchmentioning
confidence: 99%
“…Some reviews have also found low numbers of mixed methods studies in primary care [22], mental health nursing [21], and health services research [18]. In comparison, other reviews suggest mixed methods are used more often: one review of UK-funded health services research found that 18% of studies are mixed methods [17]; nursing and education journals publish more mixed methods studies (16%) than psychology and sociology journals (6%) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have described the prevalence and quality of mixed methods studies in health services research [16][17][18], social and behavioural sciences [19,20], and various biomedical disciplines [21][22][23]. The purpose of this review was to provide a critical overview of the current state of mixed methods research in CAM.…”
Section: Introductionmentioning
confidence: 99%